Flood inundation modeling in ungauged basins using Unmanned Aerial Vehicles imagery - Yavari, Adel; Homayouni, Saeid; Oubennaceur, Khalid; Chokmani, Karem (Earth Observation and Geomatics Engineering, 2020)
This paper presents a new framework for floodplain inundation modeling in an ungauged basin using unmanned aerial vehicles (UAVs) imagery. This method is based on the integrated analysis of high-resolution ortho-images and elevation data produced by the structure from motion (SfM) technology. To this end, the Flood-Level Marks (FLMs) were created from high-resolution UAV ortho-images and compared to the flood inundated areas simulated using the HEC-RAS hydraulic model. The flood quantiles for 25, 50, 100, and 200 return periods were then estimated by synthetic hydrographs using the Natural Resources Conservation Service (NRCS). The proposed method was applied to UAV image data collected from the Khosban village, in Taleghan County, Iran, in the ungauged sub-basin of the Khosban River. The study area is located along one kilometre of the river in the middle of the village. The results showed that the flood inundation areas modeled by the HEC-RAS were 33%, 19%, and 8% less than those estimated from the UAV’s FLMs for 25, 50, and 100 years return periods, respectively. For return periods of 200 years, this difference was overestimated by more than 6%, compared to the UAV’s FLM. The maximum flood depth in our four proposed scenarios of hydraulic models varied between 2.33 to 2.83 meters. These analyses showed that this method, based on the UAV imagery, is well suited to improve the hydraulic modeling for seasonal inundation in ungauged rivers, thus providing reliable support to flood mitigation strategies

Imaging Floods and Glacier Geohazards with Remote Sensing - Cigna, Francesca; Xie, Hongjie (Remote Sensing, 2020)
Geohazards associated with the dynamics of the liquid and solid water of the Earth’s hydrosphere, such as floods and glacial processes, may pose significant risks to populations, activities and properties [...]

Information Seeking and Information Sharing Related to Hurricane Harvey - Yang, Janet Z.; Zhuang, Jun (Journalism & Mass Communication Quarterly, 2020)
This study is focused on social cognitive variables that motivate information seeking and information sharing related to Hurricane Harvey. Survey results from a nationally representative sample and a quota sample of Houston residents indicate that climate change beliefs and issue salience are consistent predictors of risk perception, which increases individuals’ negative emotions and information insufficiency. This need for information subsequently motivates information seeking and information sharing. Informational subjective norms are significantly related to seeking and sharing in the Houston sample, whereas perceived information gathering capacity and trust in media are significant predictors in the national sample.

The role of public relations in building community resilience to natural disasters: perspectives from Sri Lanka and New Zealand - Dharmasena, M. K. Gayadini Imesha; Toledano, Margalit; Weaver, C. Kay (Journal of Communication Management, 2020)
The paper identifies a role for public relations in disaster management by analysing disaster and communication managers' understanding of community resilience and their use of communication in the context of two different cultural environments.,The research study comprised 51 in-depth qualitative interviews with disaster managers in Sri Lanka and New Zealand, which were thematically analysed using the software programme NVivo 10.,The study identified cultural differences in Sri Lanka and New Zealand that impact on how managers' communicate in natural disaster situations. The findings indicated that public relations’ understanding of communities’ cultures, their communication, networking and lobbying skills could further enhance the effectiveness of efforts to build community resilience to disasters.,Nations are complex multicultural realities; the findings cannot be generalized to make claims about how natural disasters are managed in different national contexts.,The paper identifies the unrealized potential of public relations’ expertise in communication, community relations, networking and lobbying to contribute to building community resilience to natural disasters.,By supporting efforts to build community resilience to disasters, public relations practitioners can contribute to social well-being in times of catastrophic natural disasters.,The paper adds an innovative perspective to public relations crisis literature by identifying the potential contribution of public relations’ concepts and practices to build community resilience to natural disasters. It demonstrates how sociocultural differences may affect disaster communication strategies.

Personal Stories Can Shift Climate Change Beliefs and Risk Perceptions: The Mediating Role of Emotion - Gustafson, Abel; Ballew, Matthew T.; Goldberg, Matthew H.; Cutler, Matthew J.; Rosenthal, Seth A.; Leiserowitz, Anthony (Communication Reports, 2020)

Short-term water quality variable prediction using a hybrid CNN–LSTM deep learning model - Barzegar, Rahim; Aalami, Mohammad Taghi; Adamowski, Jan (Stochastic Environmental Research and Risk Assessment, 2020)

Normative Influences on Farmers’ Intentions to Practice Conservation Without Compensation - Vaske, Jerry J.; Landon, Adam C.; Miller, Craig A. (Environmental Management, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Stream habitat provided by large wood at risk under drainage law - Shirey, Patrick D.; Kenny, Jillian B.; Brueseke, Michael A.; Lamberti, Gary A. (Earth Surface Processes and Landforms, 2020)
Watershed management efforts in agriculturally dominated landscapes of North America face nearly two centuries of laws and policies that encouraged habitat destruction. Although streams and wetlands in these landscapes are actively being restored using designs that incorporate science and engineering, watershed drainage laws can constrain action or impact passively restored or naturalized habitat. In general, drainage laws require removal of any riparian vegetation or wood deemed to obstruct flow in streams regulated as drains. We use a case study from Indiana (USA) to introduce the shortcomings of drainage laws for allowing large wood, which is an important habitat feature, to remain in stream ecosystems. Removals of large wood from monitored stream reaches in a regulated drain were associated with subsequent declines in fish biomass. Such legal activities represent an important environmental management problem that exists under drainage laws which apply to streams over a widespread geographic region of North America. Recent litigation in Wisconsin (USA) suggests that if state legislatures fail to update these antiquated laws, the courts may act in favour of science-based management of drains. The statutes and regulations that govern agricultural drainage warrant careful consideration if streams within drainage districts are to be managed to improve ecological function. © 2020 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

The ERA5 global reanalysis - Hersbach, Hans; Bell, Bill; Berrisford, Paul; Hirahara, Shoji; Horányi, András; Muñoz‐Sabater, Joaquín; Nicolas, Julien; Peubey, Carole; Radu, Raluca; Schepers, Dinand; Simmons, Adrian; Soci, Cornel; et al. (Quarterly Journal of the Royal Meteorological Society, 2020)
Abstract Within the Copernicus Climate Change Service (C3S), ECMWF is producing the ERA5 reanalysis which, once completed, will embody a detailed record of the global atmosphere, land surface and ocean waves from 1950 onwards. This new reanalysis replaces the ERA‐Interim reanalysis (spanning 1979 onwards) which was started in 2006. ERA5 is based on the Integrated Forecasting System (IFS) Cy41r2 which was operational in 2016. ERA5 thus benefits from a decade of developments in model physics, core dynamics and data assimilation. In addition to a significantly enhanced horizontal resolution of 31 km, compared to 80 km for ERA‐Interim, ERA5 has hourly output throughout, and an uncertainty estimate from an ensemble (3‐hourly at half the horizontal resolution). This paper describes the general set‐up of ERA5, as well as a basic evaluation of characteristics and performance, with a focus on the dataset from 1979 onwards which is currently publicly available. Re‐forecasts from ERA5 analyses show a gain of up to one day in skill with respect to ERA‐Interim. Comparison with radiosonde and PILOT data prior to assimilation shows an improved fit for temperature, wind and humidity in the troposphere, but not the stratosphere. A comparison with independent buoy data shows a much improved fit for ocean wave height. The uncertainty estimate reflects the evolution of the observing systems used in ERA5. The enhanced temporal and spatial resolution allows for a detailed evolution of weather systems. For precipitation, global‐mean correlation with monthly‐mean GPCP data is increased from 67% to 77%. In general, low‐frequency variability is found to be well represented and from 10 hPa downwards general patterns of anomalies in temperature match those from the ERA‐Interim, MERRA‐2 and JRA‐55 reanalyses.
Keywords: Ouvrage_Collectif_Numéro1

The human cost of disasters: an overview of the last 20 years (2000-2019) - UNDRR (UN Office for Disaster Risk Reduction, 2020)
UNDRR report published to mark the International Day for Disaster Risk Reduction on October 13, 2020, confirms how extreme weather events have come to dominate the disaster landscape in the 21st century.
Keywords: Ouvrage_Collectif_Numéro1

Privatizing climate adaptation: How insurance weakens solidaristic and collective disaster recovery - Lucas, Chloe H.; Booth, Kate I. (WIREs Climate Change, 2020)
Abstract As losses from extreme weather events grow, many governments are looking to privatize the financing and incentivization of climate adaptation through insurance markets. In a pure market approach to insurance for extreme weather events, individuals become responsible for ensuring they are adequately covered for risks to their own properties, and governments no longer contribute funds to post‐disaster recovery. Theoretically, insurance premiums signal the level of risk faced by each household, and incentivize homeowners to invest in adaptive action, such as retrofitting, or drainage work, to reduce premiums. Where risk is considered too high by insurance markets, housing is devalued, in theory leading to retreat from risky areas. In this review article, we evaluate the suitability of private insurance as a mechanism for climate adaptation at a household and community level. We find a mismatch between social understandings of responsibility for climate risks, and the technocratic, market‐based home insurance products offered by private insurance markets. We suggest that by constructing increasingly individualized, technical, and calculative evaluations of risk, market‐based models of insurance for extreme weather events erode the solidaristic and collective discourses and practices that support adaptive behavior. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation
Keywords: Ouvrage_Collectif_Numéro1

Estimating flood impact on residential values (housing price) : the case of Laval (Canada), 1995-2007 - Abdelhalim, Maha (2020)
Cette thèse vise à améliorer notre compréhension du modèle hédonique et de son application sur les données des biens immobiliers afin d'étudier l'impact d'un événement / externalité / environnementale liée à la présence d'inondation sur la valeur des propriétés résidentielles. Étant donné que les données immobilières sont réparties dans l'espace et dans le temps, des "corrections" temporelles et spatiales sont nécessaires dans le processus de modélisation économétrique. La recherche prend appui sur l’équation de prix hédonique. L’analyse empirique recours également à l’estimateur de type différence de différences spatio-temporelles (STDID) afin d’étudier l’effet d’une inondation survenue en 1998 sur le prix des résidences dans la ville de Laval au Canada entre 1995-2007. Les résultats suggèrent que l’utilisation des informations sur les zones inondables dans le but d’évaluer l’impact des inondations sur les valeurs résidentielles n’est pas une approche nécessairement appropriée. Les conclusions suggèrent que la grande hétérogénéité des résultats notés dans la littérature n’est probablement pas étrangère à la façon de définir les résidences touchées par les inondations. Cela signifie que les recherches empiriques sur les effets des inondations sur la valeur immobilière mesurent en réalité la valeur liée à la perception du risque d'inondation et non l’effet réel de l'inondation. Les résultats suggèrent que les applications futures dans la littérature devront porter une attention particulière à la manière de définir les zones inondables et d’identifier les résidences réellement touchées.

The language of risk and the risk of language: Mismatches in risk response in Cuban coastal villages - Aragón-Duran, Ernesto; Lizarralde, Gonzalo; González-Camacho, Gonzalo; Olivera-Ranero, Andrés; Bornstein, Lisa; Herazo, Benjamin; Labbé, Danielle (International Journal of Disaster Risk Reduction, 2020)
Keywords: Lizarralde_Gonzalo

Distributed Optical Fiber-Based Approach for Soil–Structure Interaction - Boujia, Nissrine; Schmidt, Franziska; Chevalier, Christophe; Siegert, Dominique; Pham Van Bang, Damien (Sensors, 2020)
Scour is a hydraulic risk threatening the stability of bridges in fluvial and coastal areas. Therefore, developing permanent and real-time monitoring techniques is crucial. Recent advances in strain measurements using fiber optic sensors allow new opportunities for scour monitoring. In this study, the innovative optical frequency domain reflectometry (OFDR) was used to evaluate the effect of scour by performing distributed strain measurements along a rod under static lateral loads. An analytical analysis based on the Winkler model of the soil was carefully established and used to evaluate the accuracy of the fiber optic sensors and helped interpret the measurements results. Dynamic tests were also performed and results from static and dynamic tests were compared using an equivalent cantilever model.
Keywords: PhamVanBang_Damien

Impacts of high precipitation on the energy and water budgets of a humid boreal forest - Isabelle, Pierre-Erik; Nadeau, Daniel F.; Anctil, François; Rousseau, Alain N.; Jutras, Sylvain; Music, Biljana (Agricultural and Forest Meteorology, 2020)
Keywords: Ouvrage_Collectif_Numéro1; Rousseau_Alain

Using Exploratory Structural Equation Modeling (ESEM) to Examine the Internal Structure of Posttraumatic Stress Disorder Symptoms - Fresno, Andrés; Arias, Víctor; Núñez, Daniel; Spencer, Rosario; Ramos, Nadia; Espinoza, Camila; Bravo, Patricia; Arriagada, Jessica; Brunet, Alain (The Spanish Journal of Psychology, 2020)
Abstract Several studies have reported the factor structure of posttraumatic stress disorder (PTSD) using confirmatory factor analysis (CFA). The results show models with different number of factors, high correlations between factors, and symptoms that belong to different factors in different models without affecting the fit index. These elements could suppose the existence of considerable item cross-loading, the overlap of different factors or even the presence of a general factor that explains the items common source of variance. The aim is to provide new evidence regarding the factor structure of PTSD using CFA and exploratory structural equation modeling (ESEM). In a sample of 1,372 undergraduate students, we tested six different models using CFA and two models using ESEM and ESEM bifactor analysis. Trauma event and past-month PTSD symptoms were assessed with Life Events Checklist for DSM-5 (LEC–5) and PTSD Checklist for DSM-5 (PCL–5). All six tested CFA models showed good fit indexes (RMSEA = .051–.056, CFI = .969–.977, TLI = .965–.970), with high correlations between factors ( M = .77, SD = .09 to M = .80, SD = .09). The ESEM models showed good fit indexes (RMSEA = .027–.036, CFI = .991–.996, TLI = .985–.992). These models confirmed the presence of cross-loadings on several items as well as loads on a general factor that explained 76.3% of the common variance. The results showed that most of the items do not meet the assumption of dimensional exclusivity, showing the need to expand the analysis strategies to study the symptomatic organization of PTSD.
Keywords: Brunet_Alain

We said, they said: the politics of conceptual frameworks in disasters and climate change in Colombia and Latin America - Lizarralde, Gonzalo; Páez, Holmes; Lopez, Adriana; Lopez, Oswaldo; Bornstein, Lisa; Gould, Kevin; Herazo, Benjamin; Muñoz, Lissette (Disaster Prevention and Management: An International Journal, 2020)
Purpose Few people living in informal settlements in the Global South spontaneously claim that they are “resilient” or “adapting” to disaster risk or climate change. Surely, they often overcome multiple challenges, including natural hazards exacerbated by climate change. Yet their actions are increasingly examined through the framework of resilience, a notion developed in the North, and increasingly adopted in the South. To what extent eliminate’ do these initiatives correspond to the concepts that scholars and authorities place under the resilience framework? Design/methodology/approach Three longitudinal case studies in Yumbo, Salgar and San Andrés (Colombia) serve to investigate narratives of disaster risks and responses to them. Methods include narrative analysis from policy and project documents, presentations, five workshops, six focus groups and 24 interviews. Findings The discourse adopted by most international scholars and local authorities differs greatly from that used by citizens to explain risk and masks the politics involved in disaster reduction and the search for social justice. Besides, narratives of social change, aspirations and social status are increasingly masked in disaster risk explanations. Tensions are also concealed, including those regarding the winners and losers of interventions and the responsibilities for disaster risk reduction. Originality/value Our findings confirm previous results that have shown that the resilience framework contributes to “depoliticize” the analysis of risk and serves to mask and dilute the responsibility of political and economic elites in disaster risk creation. But they also show that resilience fails to explain the type of socioeconomic change that is required to reduce vulnerabilities in Latin America.
Keywords: Lizarralde_Gonzalo

Welfare in the 21st century: Increasing development, reducing inequality, the impact of climate change, and the cost of climate policies - Lomborg, Bjorn (Technological Forecasting and Social Change, 2020)

Impacts of climate change on the hydrology of northern midlatitude cold regions - Aygün, Okan; Kinnard, Christophe; Campeau, Stéphane (Progress in Physical Geography: Earth and Environment, 2020)
Cold region hydrology is conditioned by distinct cryospheric and hydrological processes. While snowmelt is the main contributor to both surface and subsurface flows, seasonally frozen soil also influences the partition of meltwater and rain between these flows. Cold regions of the Northern Hemisphere midlatitudes have been shown to be sensitive to climate change. Assessing the impacts of climate change on the hydrology of this region is therefore crucial, as it supports a significant amount of population relying on hydrological services and subjected to changing hydrological risks. We present an exhaustive review of the literature on historical and projected future changes on cold region hydrology in response to climate change. Changes in snow, soil, and streamflow key metrics were investigated and summarized at the hemispheric scale, down to the basin scale. We found substantial evidence of both historical and projected changes in the reviewed hydrological metrics. These metrics were shown to display different sensitivities to climate change, depending on the cold season temperature regime of a given region. Given the historical and projected future warming during the 21st century, the most drastic changes were found to be occurring over regions with near-freezing air temperatures. Colder regions, on the other hand, were found to be comparatively less sensitive to climate change. The complex interactions between the snow and soil metrics resulted in either colder or warmer soils, which led to increasing or decreasing frost depths, influencing the partitioning rates between the surface and subsurface flows. The most consistent and salient hydrological responses to both historical and projected climate change were an earlier occurrence of snowmelt floods, an overall increase in water availability and streamflow during winter, and a decrease in water availability and streamflow during the warm season, which calls for renewed assessments of existing water supply and flood risk management strategies.
Keywords: Kinnard_Christophe

Housing Market Response to New Flood Risk Information and the Impact on Poor Tenant - Yi, Donggyu; Choi, Hyundo (The Journal of Real Estate Finance and Economics, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Cooperation in flood risk management: understanding the role of strategic planning in two Austrian policy instruments - Thaler, Thomas; Nordbeck, Ralf; Löschner, Lukas; Seher, Walter (Environmental Science & Policy, 2020)

Spatial Spillovers in the Pricing of Flood Risk: Insights from the Housing Market - Pommeranz, Carolin; Steininger, Bertram I. (Journal of Housing Research, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Flood management in India: A focussed review on the current status and future challenges - Mohanty, Mohit Prakash; Mudgil, Sahil; Karmakar, Subhankar (International Journal of Disaster Risk Reduction, 2020)

The behavioral turn in flood risk management, its assumptions and potential implications - Kuhlicke, Christian; Seebauer, Sebastian; Hudson, Paul; Begg, Chloe; Bubeck, Philip; Dittmer, Cordula; Grothmann, Torsten; Heidenreich, Anna; Kreibich, Heidi; Lorenz, Daniel F.; Masson, Torsten; Reiter, Jessica; et al. (WIREs Water, 2020)
Abstract Recent policy changes highlight the need for citizens to take adaptive actions to reduce flood‐related impacts. Here, we argue that these changes represent a wider behavioral turn in flood risk management (FRM). The behavioral turn is based on three fundamental assumptions: first, that the motivations of citizens to take adaptive actions can be well understood so that these motivations can be targeted in the practice of FRM; second, that private adaptive measures and actions are effective in reducing flood risk; and third, that individuals have the capacities to implement such measures. We assess the extent to which the assumptions can be supported by empirical evidence. We do this by engaging with three intellectual catchments. We turn to research by psychologists and other behavioral scientists which focus on the sociopsychological factors which influence individual motivations (Assumption 1). We engage with economists, engineers, and quantitative risk analysts who explore the extent to which individuals can reduce flood related impacts by quantifying the effectiveness and efficiency of household‐level adaptive measures (Assumption 2). We converse with human geographers and sociologists who explore the types of capacities households require to adapt to and cope with threatening events (Assumption 3). We believe that an investigation of the behavioral turn is important because if the outlined assumptions do not hold, there is a risk of creating and strengthening inequalities in FRM. Therefore, we outline the current intellectual and empirical knowledge as well as future research needs. Generally, we argue that more collaboration across intellectual catchments is needed, that future research should be more theoretically grounded and become methodologically more rigorous and at the same time focus more explicitly on the normative underpinnings of the behavioral turn. This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Science of Water > Water Extremes

Flood Damage and Mortgage Credit Risk: A Case Study of Hurricane Harvey - Kousky, Carolyn; Palim, Mark; Pan, Ying (Journal of Housing Research, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Evaluating the suitability of policy instruments for urban flood risk reduction - Henstra, Daniel; Thistlethwaite, Jason; Dordi, Truzaar (Local Environment, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Flood Risk Perception in the Housing Market and the Impact of a Major Flood Event - Hennighausen, Hannah; Suter, Jordan F. (Land Economics, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Flood Hazard Risk Mapping Using a Pseudo Supervised Random Forest - Esfandiari, Morteza; Abdi, Ghasem; Jabari, Shabnam; McGrath, Heather; Coleman, David (Remote Sensing, 2020)
Devastating floods occur regularly around the world. Recently, machine learning models have been used for flood susceptibility mapping. However, even when these algorithms are provided with adequate ground truth training samples, they can fail to predict flood extends reliably. On the other hand, the height above nearest drainage (HAND) model can produce flood prediction maps with limited accuracy. The objective of this research is to produce an accurate and dynamic flood modeling technique to produce flood maps as a function of water level by combining the HAND model and machine learning. In this paper, the HAND model was utilized to generate a preliminary flood map; then, the predictions of the HAND model were used to produce pseudo training samples for a R.F. model. To improve the R.F. training stage, five of the most effective flood mapping conditioning factors are used, namely, Altitude, Slope, Aspect, Distance from River and Land use/cover map. In this approach, the R.F. model is trained to dynamically estimate the flood extent with the pseudo training points acquired from the HAND model. However, due to the limited accuracy of the HAND model, a random sample consensus (RANSAC) method was used to detect outliers. The accuracy of the proposed model for flood extent prediction, was tested on different flood events in the city of Fredericton, NB, Canada in 2014, 2016, 2018, 2019. Furthermore, to ensure that the proposed model can produce accurate flood maps in other areas as well, it was also tested on the 2019 flood in Gatineau, QC, Canada. Accuracy assessment metrics, such as overall accuracy, Cohen’s kappa coefficient, Matthews correlation coefficient, true positive rate (TPR), true negative rate (TNR), false positive rate (FPR) and false negative rate (FNR), were used to compare the predicted flood extent of the study areas, to the extent estimated by the HAND model and the extent imaged by Sentinel-2 and Landsat satellites. The results confirm that the proposed model can improve the flood extent prediction of the HAND model without using any ground truth training data.

Efficient or Fair? Operationalizing Ethical Principles in Flood Risk Management: A Case Study on the Dutch‐German Rhine - Ciullo, Alessio; Kwakkel, Jan H.; De Bruijn, Karin M.; Doorn, Neelke; Klijn, Frans (Risk Analysis, 2020)
Abstract Flood risk management decisions in many countries are based on decision‐support frameworks which rely on cost‐benefit analyses. Such frameworks are seldom informative about the geographical distribution of risk, raising questions on the fairness of the proposed policies. In the present work, we propose a new decision criterion that accounts for the distribution of risk reduction and apply it to support flood risk management decisions on a transboundary stretch of the Rhine River. Three types of interventions are considered: embankment heightening, making Room for the River, and changing the discharge distribution of the river branches. The analysis involves solving a flood risk management problem according to four alternative formulations, based on different ethical principles. Formulations based on cost optimization lead to very poor performances in some areas for the sake of reducing the overall aggregated costs. Formulations that also include equity criteria have different results depending on how these are defined. When risk reduction is distributed equally, very poor economic performance is achieved. When risk is distributed equally, results are in line with formulations based on cost optimization, while a fairer risk distribution is achieved. Risk reduction measures also differ, with the cost optimization approach strongly favoring the leverage of changing the discharge distribution and the alternative formulations spending more on embankment heightening and Room for the River, to rebalance inequalities in risk levels. The proposed method advances risk‐based decision‐making by allowing to consider risk distribution aspects and their impacts on the choice of risk reduction measures.

Natural disasters and risk aversion - Bourdeau-Brien, Michael; Kryzanowski, Lawrence (Journal of Economic Behavior & Organization, 2020)
Keywords: Bourdeau-Brien_Michael; Ouvrage_Collectif_Numéro1

Overview of Retrogressive Landslide Risk Analysis in Sensitive Clay Slope - Richer, Blanche; Saeidi, Ali; Boivin, Maxime; Rouleau, Alain (Geosciences, 2020)
Sensitive clays are known for producing retrogressive landslides, also called spread or flowslides. The key characteristics associated with the occurrence of these landslides on a sensitive clay slope must be assessed, and the potential retrogressive distance must be evaluated. Common risk analysis methods include empirical methods for estimating the distance of potential retrogression, analytical limit equilibrium methods, numerical modelling methods using the strength reduction technique, and the integration of a progressive failure mechanism into numerical methods. Methods developed for zoning purposes in Norway and Quebec provide conservative results in most cases, even if they don’t cover the worst cases scenario. A flowslide can be partially analysed using analytical limit equilibrium methods and numerical methods having strength reduction factor tools. Numerical modelling of progressive failure mechanisms using numerical methods can define the critical parameters of spread-type landslides, such as critical unloading and the retrogression distance of the failure. Continuous improvements to the large-deformation numerical modeling approach allow its application to all types of sensitive clay landslides.
Keywords: Boivin_Maxime

Large Scale Flood Risk Mapping in Data Scarce Environments: An Application for Romania - Albano, Raffaele; Samela, Caterina; Crăciun, Iulia; Manfreda, Salvatore; Adamowski, Jan; Sole, Aurelia; Sivertun, Åke; Ozunu, Alexandru (Water, 2020)
Large-scale flood risk assessment is essential in supporting national and global policies, emergency operations and land-use management. The present study proposes a cost-efficient method for the large-scale mapping of direct economic flood damage in data-scarce environments. The proposed framework consists of three main stages: (i) deriving a water depth map through a geomorphic method based on a supervised linear binary classification; (ii) generating an exposure land-use map developed from multi-spectral Landsat 8 satellite images using a machine-learning classification algorithm; and (iii) performing a flood damage assessment using a GIS tool, based on the vulnerability (depth–damage) curves method. The proposed integrated method was applied over the entire country of Romania (including minor order basins) for a 100-year return time at 30-m resolution. The results showed how the description of flood risk may especially benefit from the ability of the proposed cost-efficient model to carry out large-scale analyses in data-scarce environments. This approach may help in performing and updating risk assessments and management, taking into account the temporal and spatial changes in hazard, exposure, and vulnerability.

A participatory system dynamics modeling approach to facilitate collaborative flood risk management: A case study in the Bradano River (Italy) - Perrone, Antonio; Inam, Azhar; Albano, Raffaele; Adamowski, Jan; Sole, Aurelia (Journal of Hydrology, 2020)

A rasterized building footprint dataset for the United States - Heris, Mehdi P.; Foks, Nathan Leon; Bagstad, Kenneth J.; Troy, Austin; Ancona, Zachary H. (Scientific Data, 2020)
Abstract Microsoft released a U.S.-wide vector building dataset in 2018. Although the vector building layers provide relatively accurate geometries, their use in large-extent geospatial analysis comes at a high computational cost. We used High-Performance Computing (HPC) to develop an algorithm that calculates six summary values for each cell in a raster representation of each U.S. state, excluding Alaska and Hawaii: (1) total footprint coverage, (2) number of unique buildings intersecting each cell, (3) number of building centroids falling inside each cell, and area of the (4) average, (5) smallest, and (6) largest area of buildings that intersect each cell. These values are represented as raster layers with 30 m cell size covering the 48 conterminous states. We also identify errors in the original building dataset. We evaluate precision and recall in the data for three large U.S. urban areas. Precision is high and comparable to results reported by Microsoft while recall is high for buildings with footprints larger than 200 m2 but lower for progressively smaller buildings.
Keywords: Ouvrage_Collectif_Numéro1

Monitoring the evolution of individuals’ flood-related adaptive behaviors over time: two cross-sectional surveys conducted in the Province of Quebec, Canada - Valois, Pierre; Tessier, Maxime; Bouchard, David; Talbot, Denis; Morin, Alexandre J. S.; Anctil, François; Cloutier, Geneviève (BMC Public Health, 2020)
Abstract Climate change is predicted to increase the frequency and intensity of floods in the province of Quebec, Canada. Therefore, in 2015, to better monitor the level of adaptation to flooding of Quebec residents living in or near a flood-prone area, the Quebec Observatory of Adaptation to Climate Change developed five indices of adaptation to flooding, according to the chronology of events. The present study was conducted 4 years later and is a follow-up to the 2015 one. Two independent samples of 1951 (2015) and 974 (2019) individuals completed a questionnaire on their adoption (or non-adoption) of flood adaptation behaviors, their perception of the mental and physical impacts of flooding, and their knowledge of the fact that they lived in a flood-prone area. The results of the study demonstrated the measurement invariance of the five indices across two different samples of people over time, ensuring that the differences (or absence of differences) observed in flood-related adaptive behaviors between 2015 and 2019 were real and not due to measurement errors. They also showed that, overall, Quebeckers’ flood-related adaptive behaviors have not changed considerably since 2015, with adaptation scores being similar in 2019 for four of the five flood indices. Moreover, the results indicated an increase in self-reported physical and mental health issues related to past flooding events, as well as a larger proportion of people having consulted a health professional because of these problems. Thus, this study provides a better understanding of flood adaptation in Quebec over the past 4 years and confirms that the five adaptive behavior indices developed in 2015 are appropriate tools for monitoring changes in flood adaptation in the province. Finally, our results showed that little has changed in Quebeckers’ adoption of adaptive behaviors, highlighting the need for awareness raising in order to limit the impacts that climate change will have on the population.

Development of a mapping approach encompassing most fluvial processes: Lessons learned from the freedom space for rivers concept in Quebec (Canada) - Massé, Simon; Demers, Sylvio; Besnard, Clément; Buffin‐Bélanger, Thomas; Biron, Pascale M.; Choné, Guénolé; Massey, William (River Research and Applications, 2020)
Abstract The consensus around the need for a shift in river management approaches to include more natural processes is steadily growing amongst scientists, practitioners, and governmental agencies. The freedom space for rivers concept promotes the delineation of a single space that integrates multiple fluvial dynamics such as floods, lateral migration, channel avulsions, and riparian wetlands connectivity. The objective of this research is to assess the validity of the hydrogeomorphological approach to delineate the freedom space for an extensive sampling of river reaches, covering 167 km, in contrasting watersheds in Quebec (Canada). Comparative analysis was conducted on the relative importance of erosion and flood processes on the freedom space delineation for various fluvial types. Semiautomated tools based on light detection and ranging (LiDAR) digital elevation models were also tested on an additional 274 km of watercourses to facilitate freedom space mapping over extensive zones and for highly dynamics environments such as alluvial fans. In the studied reaches, flood and erosion processes occur respectively, on average, in a space equivalent to 2.6 and 20.6 channel widths. In unconfined landscapes, flood processes represent an area up to almost four times the area of erosion processes expected in a 50‐year period. In partly confined and confined environments, erosion processes are more likely to exceed flooding zone, and therefore need to be integrated in the mapping. This study helps better determine the conditions for which the full methodology of freedom space mapping is required or where semiautomated methods can be used. It provides useful guidelines for the implementation of the freedom space approach.
Keywords: Ouvrage_Collectif_Numéro1

Current and Projected Distributions of Aedes aegypti and Ae. albopictus in Canada and the U.S. - Khan, Salah Uddin; Ogden, Nicholas H.; Fazil, Aamir A.; Gachon, Philippe H.; Dueymes, Guillaume U.; Greer, Amy L.; Ng, Victoria (Environmental Health Perspectives, 2020)
Keywords: Gachon_Philippe

Evaluating the Dependence between Temperature and Precipitation to Better Estimate the Risks of Concurrent Extreme Weather Events - Wazneh, Hussein; Arain, M. Altaf; Coulibaly, Paulin; Gachon, Philippe (Advances in Meteorology, 2020)
Precipitation and temperature are among major climatic variables that are used to characterize extreme weather events, which can have profound impacts on ecosystems and society. Accurate simulation of these variables at the local scale is essential to adapt urban systems and policies to future climatic changes. However, accurate simulation of these climatic variables is difficult due to possible interdependence and feedbacks among them. In this paper, the concept of copulas was used to model seasonal interdependence between precipitation and temperature. Five copula functions were fitted to grid (approximately 10 km × 10 km) climate data from 1960 to 2013 in southern Ontario, Canada. Theoretical and empirical copulas were then compared with each other to select the most appropriate copula family for this region. Results showed that, of the tested copulas, none of them consistently performed the best over the entire region during all seasons. However, Gumbel copula was the best performer during the winter season, and Clayton performed best in the summer. More variability in terms of best copula was found in spring and fall seasons. By examining the likelihoods of concurrent extreme temperature and precipitation periods including wet/cool in the winter and dry/hot in the summer, we found that ignoring the joint distribution and confounding impacts of precipitation and temperature lead to the underestimation of occurrence of probabilities for these two concurrent extreme modes. This underestimation can also lead to incorrect conclusions and flawed decisions in terms of the severity of these extreme events.
Keywords: Gachon_Philippe

Multivariate extremes and compound events - Zscheischler, Jakob; Van Den Hurk, Bart; Ward, Philip J.; Westra, Seth (Climate Extremes and Their Implications for Impact and Risk Assessment, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Adoption of flood-related preventive behaviours by people having different risks and histories of flooding - Valois, Pierre; Bouchard, David; Talbot, Denis; Caron, Maxime; Renaud, Jean-Sébastien; Gosselin, Pierre; Jacob, Johann (Natural Hazards, 2020)
The increase in the frequency of floods, which is a projected consequence of climate change, can have wide-ranging health and economic impacts. To cope with these floods and to reduce their impacts, households can adopt some preventive behaviours. The main goal of this research was to compare the adoption of flood mitigation behaviours in three populations presenting distinctive characteristics with a valid and an invariant measure of behavioural adaptation, as well as a baseline measure (comparison group). The article also aims to test the moderated effect of having experienced a flood on the relation between the perception of risk of being flooded and the adoption of preventive behaviours. A survey was conducted in flood-prone areas and in some areas that were not at risk in Quebec, Canada, through phone interviews. Results confirmed that people who lived in an at-risk area and had experienced past flooding events are more inclined to adopt preventive behaviours than people who lived in an at-risk area but had never experienced such an event, and those who lived outside at-risk areas. In addition, our results indicate that the at-risk population who have never experienced a flood engage in few flood preventive behaviours. This is worrisome, as their rate of adopting adaptive behaviour is very similar to the one seen in populations living outside at-risk areas, despite the increased risk inherent to their situation. This could be partly explained by our data showing that around a quarter of the at-risk population did not know they were living in a flood-prone area. Our results show that communication efforts are necessary in order to better inform the population of the risk related to living in a flood-prone area and that incentives should be developed to help enhance the rate of preventive behaviours in at-risk populations having never experienced a flood.

Barriers to Insurance as a Flood Risk Management Tool: Evidence from a Survey of Property Owners - Thistlethwaite, Jason; Henstra, Daniel; Brown, Craig; Scott, Daniel (International Journal of Disaster Risk Science, 2020)
Abstract By using risk-adjusted price signals to transfer responsibility for property-level flood protection and recovery from governments to property owners, flood insurance represents a key tenet of the flood risk management (FRM) paradigm. The Government of Canada has worked with insurers to introduce flood insurance for the first time as a part of a broader shift towards FRM to limit the growing costs of flooding. The viability of flood insurance in Canada, however, has been questioned by research that disputes the utility of purchasing coverage by property owners. This study tested this assumption by drawing on public opinion survey data to assess factors that influence decisions about the utility of insurance. The findings reveal that Canadians have limited knowledge of flood insurance coverage, exhibit a low willingness-to-pay for both insurance and property-level flood protection measures, and expect governments to shoulder much of the financial burden of flood recovery through disaster assistance.
Keywords: Ouvrage_Collectif_Numéro1

Disrupting the riskscapes of inequities: a case study of planning for resilience in Canada’s Metro Vancouver region - Yumagulova, Lilia (Cambridge Journal of Regions, Economy and Society, 2020)
Abstract The analysis across spatial, temporal and governance scales shows an inequitable distribution of risk across Canada’s Metro Vancouver region. For First Nation communities in this region, this risk is rooted in the colonial history of land dispossession. This article makes a contribution by expanding our understanding of historic creation of riskscapes and a discussion of its implications as a multiscale governance issue that persists across space and time. This article also situates the impacts of projected sea level rise on Indigenous communities in the context of regional, provincial and federal settler-colonial flood risk management regime.

Operating urban resilience strategies to face climate change and associated risks: some advances from theory to application in Canada and France - Heinzlef, Charlotte; Robert, Benoît; Hémond, Yannick; Serre, Damien (Cities, 2020)
Keywords: Hémond_Yannick; Ouvrage_Collectif_Numéro1

Retrofitting for Flood Resilience: A Guide to Building & Community Design - Barsley, Edward (RIBA Publishing, 2020)
Keywords: Ouvrage_Collectif_Numéro1

The Economic Impacts of Direct Natural Disaster Exposure - Johar, Meliyanni; Johnston, David W.; Shields, Michael; Siminski, Peter; Stavrunova, Olena (SSRN Electronic Journal, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Measuring social equity in flood recovery funding - Emrich, Christopher T.; Tate, Eric; Larson, Sarah E.; Zhou, Yao (Environmental Hazards, 2020)

Leveraging public adaptation finance through urban land reclamation: cases from Germany, the Netherlands and the Maldives - Bisaro, Alexander; De Bel, Mark; Hinkel, Jochen; Kok, Sien; Bouwer, Laurens M. (Climatic Change, 2020)

Neglecting uncertainties biases house-elevation decisions to manage riverine flood risks - Zarekarizi, Mahkameh; Srikrishnan, Vivek; Keller, Klaus (Nature Communications, 2020)
Abstract Homeowners around the world elevate houses to manage flood risks. Deciding how high to elevate a house poses a nontrivial decision problem. The U.S. Federal Emergency Management Agency (FEMA) recommends elevating existing houses to the Base Flood Elevation (the elevation of the 100-year flood) plus a freeboard. This recommendation neglects many uncertainties. Here we analyze a case-study of riverine flood risk management using a multi-objective robust decision-making framework in the face of deep uncertainties. While the quantitative results are location-specific, the approach and overall insights are generalizable. We find strong interactions between the economic, engineering, and Earth science uncertainties, illustrating the need for expanding on previous integrated analyses to further understand the nature and strength of these connections. Considering deep uncertainties surrounding flood hazards, the discount rate, the house lifetime, and the fragility can increase the economically optimal house elevation to values well above FEMA’s recommendation.
Keywords: Ouvrage_Collectif_Numéro1

From Policy Challenge to Implementation Strategy: Enabling Strategies for Network Governance of Urban Resilience - Therrien, Marie‐Christine; Normandin, Julie‐Maude (Risk, Hazards & Crisis in Public Policy, 2020)
What transformations do municipal administrations implement to enact a resilience policy? This article responds to this question from a comparative perspective by analyzing enabling and impeding mechanisms developed in the cities of Montreal (Canada) and London (UK) as they establish their strategies. Collaborative network governance and institutional work mechanisms used in Montreal and London are analyzed in connection with the influence of macro‐ and micro‐contextual elements under which a network can resiliently manage risk and crises. In both cases, the development of resilience emerges from their emergency management structures, as units in charge try to animate their new area of responsibility through collaborative governance. As a siloed approach this is embedded in daily routines, organizations with limited resources focused on shared motivation and values, collaboration across organizational boundaries and creation of joint capacity to implement resilience. This transformative process concerns the organization in charge of resilience in the municipal administration and the wider network that they build and animate. , 从政策挑战到落实战略: 为都市韧性网络管理创造战略 自治政府为颁布一项韧性政策会经历哪些转型?本文透过比较视角, 通过分析蒙特利尔(加拿大)和伦敦(英国)在建立各自战略时开发的推动机制和阻碍机制, 对该疑问进行了回应。分析了蒙特利尔和伦敦所使用的协作网络治理及机构工作机制与“宏观和微观情境元素的影响”之间的关系, 在这些情境元素中网络能发挥韧性管理风险和危机。在这两个案例中, 当应急管理结构中各主管单位试图通过协作治理开启新的责任区时, 韧性便得以发展。作为一项孤立的措施, 其被应用于日常活动中、应用于在共享动机和价值观方面资源有限的机构中、还被用于跨组织界限的协作以及为发挥韧性而创造的共同行动。该转型过程与负责自治政府韧性建设的机构有关, 还与后者建立和推动的更广网络有关。 , Del desafío político a la estrategia de implementación: estrategias habilitantes para la gobernanza de la red de resiliencia urbana ¿Qué transformaciones implementan las administraciones municipales para promulgar una política de resiliencia? Este artículo responde a esta pregunta desde una perspectiva comparativa analizando los mecanismos habilitadores e impedidores desarrollados en las ciudades de Montreal (Canadá) y Londres (Reino Unido) a medida que establecen sus estrategias. La gobernanza de la red colaborativa y los mecanismos de trabajo institucional utilizados en Montreal y Londres se analizan en relación con la influencia de elementos macro y micro contextuales bajo los cuales una red puede gestionar de manera resiliente los riesgos y las crisis. En ambos casos, el desarrollo de la resiliencia surge de sus estructuras de gestión de emergencias, ya que las unidades a cargo intentan animar su nueva área de responsabilidad a través de la gobernanza colaborativa. Como un enfoque aislado, esto se integra en las rutinas diarias, las organizaciones con recursos limitados se centraron en la motivación y los valores compartidos, la colaboración a través de los límites de la organización y la creación de capacidad conjunta para implementar la resiliencia. Este proceso transformador concierne a la organización a cargo de la resiliencia en la administración municipal y la red más amplia que construyen y animan.

Démarche de gouvernance collaborative d'appréciation des risques des systèmes essentiels - Baril, G.; Hémond, Y.; Lépine, C.; Préval, J.; Robert, B.; Therrien, M.-C. (2020)
schéma de couverture de risques et schéma d’aménagement et de développement), visant à développer de manière concertée avec les municipalités locales une vision commune et une planification conjointe, la MRC est la structure administrative qui, dans le cadre de l’appréciation des risques des SE, pourrait intégrer les principes de gouvernance multiniveau et de gouvernance horizontale. [...] 3.1.5 Le suivi et la révision Un système de suivi avec des indicateurs de performance doit être mis en place dans le but de valider toutes les étapes du processus de gestion des risques, la justesse des évaluations et des priorités établies ainsi que l’efficacité des mesures implantées et l’atteinte des objectifs fixés. [...] La composante "planification" correspond à l’élaboration de plans de mesures d’urgence, de plans de continuité des opérations et de plans de sécurité des actifs établis à l’issue des processus de gestion des risques. [...] Ce cadre théorique fait écho à l’approche globale et intégrée de la sécurité civile du Ministère de la sécurité publique qui repose sur trois principes « la prise en compte de tous les aléas, l’adoption de mesures couvrant les quatre dimensions de la sécurité ́civile et des actions concertées de tous les acteurs à tous les niveaux. [...] 32 Figure 1 - Extrait de la base de données de la MRC d’Argenteuil Figure 2 - Extrait de la base de données de la MRC de Brome-Missisquoi Fait saillant Malgré une bonne connaissance de son territoire par la MRC, la contribution des municipalités locales est fondamentale pour assurer un inventaire détaillé des SE.
Keywords: Hémond_Yannick

Governance for Flood Risk Reduction: Assessing Quebec’s Special Planning Zone Approach to Landowner Compensations and Restricted Redevelopment - Bornstein, L.; Merkoukhina, K. (2020)

The Hazards of Mainstreaming: Climate change adaptation politics in three dimensions - Scoville-Simonds, Morgan; Jamali, Hameed; Hufty, Marc (World Development, 2020)

A place-based socioeconomic status index: Measuring social vulnerability to flood hazards in the context of environmental justice - Chakraborty, Liton; Rus, Horatiu; Henstra, Daniel; Thistlethwaite, Jason; Scott, Daniel (International Journal of Disaster Risk Reduction, 2020)
Keywords: Ouvrage_Collectif_Numéro1